18F-fluorodeoxyglucose positron emission tomography in dementia with Lewy bodies. Issue 1 (8th April 2020) - Graff-Radford, Jonathan; Lesnick, Timothy G; Savica, Rodolfo; Chen, Qin; Ferman, Tanis J; Przybelski, Scott A; Jones, David T; Senjem, Matthew L; Gunter, Jeffrey L; Kremers, Walter K; Jack, Clifford R; Lowe, Val J; et al.
Abstract: Among individuals with dementia with Lewy bodies, pathologic correlates of clinical course include the presence and extent of coexisting Alzheimer's pathology and the presence of transitional or diffuse Lewy body disease. The objectives of this study are to determine (i) whether 18 F-fluorodeoxyglucose PET signature patterns of dementia with Lewy bodies are associated with the extent of coexisting Alzheimer's pathology and the presence of transitional or diffuse Lewy body disease and (ii) whether these 18 F-fluorodeoxyglucose pattern(s) are associated with clinical course in dementia with Lewy bodies. Two groups of participants were included: a pathology-confirmed subset with Lewy body disease ( n = 34) and a clinically diagnosed group of dementia with Lewy bodies ( n = 87). A subset of the clinically diagnosed group was followed longitudinally ( n = 51). We evaluated whether 18 F-fluorodeoxyglucose PET features of dementia with Lewy bodies (higher cingulate island sign ratio and greater occipital hypometabolism) varied by Lewy body disease subtype (transitional versus diffuse) and Braak neurofibrillary tangle stage. We investigated whether the PET features were associated with the clinical trajectories by performing regression models predicting Clinical Dementia Rating Scale Sum of Boxes. Among autopsied participants, there was no difference in cingulate island sign or occipital hypometabolism by Lewy body disease type, but those with a lower Braak tangle stage had a higher cingulate island sign ratio compared to those with a higher Braak tangle stage. Among the clinically diagnosed dementia with Lewy bodies participants, a higher cingulate island ratio was associated with better cognitive scores at baseline and longitudinally. A higher 18 F-fluorodeoxyglucose PET cingulate island sign ratio was associated with lower Braak tangle stage at autopsy, predicted a better clinical trajectory in dementia with Lewy body patients and may allow for improved prognostication of the clinical course in this disease. Abstract : In dementia with Lewy bodies, a higher cingulate island sign ratio on 18 F-fluorodeoxyglucose PET was associated with a lower Braak neurofibrillary tangle stage. We investigated whether the cingulate island sign was associated with clinical trajectory. A higher cingulate island sign ratio was associated with better cognition at baseline and longitudinally. Graphical Abstract: